Natchez burning : a novel - Iles, Greg (Penn Cage series, 2014)
Penn Cage must investigate when his father, a beloved family doctor and pillar of the community, is accused of murdering Violet Davis, the beautiful nurse with whom he worked in the dark days of the early 1960s.